Original sin and the CFA Franc: A case study of the West African Economic and Monetary Union - Moritz Manuel Peist (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2023)
This paper investigates Original Sin in the West African Economic and Monetary Union in the framework of regional integration and cooperation initiatives. The phenomenon describes the inability of countries to borrow in their currency. The central hypothesis is that smaller South-South Coordination schemes do not possess the necessary magnitude to overcome Original Sin. The paper first substantiates the existence of Original Sin in West Africa. It then examines the influence of economic, fiscal, and monetary factors on the time variance of Original Sin in the region using a Tobit model. The results delivered mixed outcomes but confirm Original Sin's negative correlation with country size. The results uphold the hypothesis that financial and monetary integration and cooperation alone are not a panacea for Original Sin.
Keywords: C33; C34; F3; F4; F6; 330; Original Sin; WAEMU; CFA Franc; Tobit